The Effectiveness of Digital Comic-Based Fantasy Story Teaching Materials in Indonesian Language Learning - Fendi, Hasri; Delami; Razak, Mohamed Razeef Abdul (Language Pedagogy Study Program, Faculty of Languages and Arts, Universitas Negeri Padang, Indonesia, 2025)
Learning Indonesian fantasy story texts often faces obstacles in improving students' understanding due to the limitations of conventional learning media. Integration of digital comics based on local culture is an innovative alternative to increase students' engagement and understanding of fantasy story texts. This study aims to explain the effectiveness of using digital comics based on local culture in learning to understand fantasy story texts. The method used is Research & Development (R&D) with the ADDIE development model, and product trials were conducted on class VII.E students of SMP Negeri 2 Padang with a one-group pretest-posttest design. The sample was selected based on the class with the lowest standard deviation. The results showed that there was a significant increase in students' understanding after using digital comics, as evidenced by the statistically significant difference in pretest and posttest scores. Digital comics have been shown to increase student engagement and overcome the limitations of conventional media. In conclusion, the use of digital comics based on local culture is effective in improving students' understanding of fantasy story texts. The results of this study indicate that innovation in technology-based learning media can be a solution to increase the effectiveness of Indonesian language learning in the digital era.